Dual-Energy SPECT and the Development of Peptide p5+14 for Imaging Amyloidosis - Jonathan S. Wall PhD; Stephen J. Kennel PhD; Emily B. Martin PhD (Molecular Imaging)
Amyloidosis is associated with a number of rare diseases and is characterized by the deposition, in abdominothoracic organs and peripheral nerves, of extracellular protein fibrils, which leads to dysfunction and severe morbidity. Effective clinical evaluation and management of patients with systemic amyloidosis are hampered by the lack of a noninvasive, quantitative method for detecting whole-body amyloid load. We have used a battery of assays including dual-energy SPECT imaging and comparative effectiveness studies in support of translation of a synthetic polybasic peptide, p5+14, as a novel radiotracer for visualization of amyloidosis by molecular imaging. These data provide support for a phase 1 positron emission tomography/computed tomography imaging trial of this reagent, labeled with iodine-124, in patients with all forms of systemic amyloidosis.